Evaluation of the histopathology results of patients operated due to Ovarian Mass - Pervin Karlı; Asuman Kilitci (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2019)
Introduction: Ovarian masses quite frequently appear before us in gynecological practice. In the present study, our purpose was to determine the types and age range of masses detected in ovarian surgeries in and around the city of Kırsehir.  Material and Methods: The study was conducted in the retrospective fashion on the pathology reports of 93 patients, who had histopathological examination in the pathology clinic due to ovarian mass between January 2015 and July 2018. The diagnoses of the patients were divided in pathological terms into 5 groups as the epithelial tumors, sex-cord stromal tumors, germ-cell tumors, other primary tumor groups, and ovarian pathologies that were not neoplastic. Results: Epithelial tumors were determined to be 38.7%, sex-cord stromal tumors were 8.6%, germ-cell tumors were 4.3%, other primary tumor group was 1.1%, and ovarian pathologies that were not neoplastic were 47.3%. When the age groups were evaluated, it was determined that the rates were 9.6% in the 10-20 age range; 12.9% in the 21-30 age range; 35.4% in the 31-40 age range; 30.1% in the 41-50 age range; and 11.8% in the 51+ age group. Conclusion: In surgeries carried out due to reasons that are not malign in the ovary, approximately half of these surgeries are carried out because of the temporary ovarian pathologies.